2018
DOI: 10.1039/c8cp03814g
|View full text |Cite
|
Sign up to set email alerts
|

An extended excited-state intramolecular proton transfer (ESIPT) emitter for random lasing applications

Abstract: An original molecular fluorophore displaying single keto (K*) excited-state intramolecular proton transfer (ESIPT) emission is presented in this article. Substitution at the 3 and 5 positions of the phenol ring of a 2-(2'-hydroxyphenylbenzoxazole) (HBO) dye by triethylsilyl-ethynyl fragments leads to a drastic enhancement of fluorescence in the solution-state as compared to unsubstituted analogues. This intense fluorescence emission is also retained in a protic solvent like ethanol and in the solid-state as em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…In these pores, there can be found aggregated SAA molecules, favoring the stabilization of cis-keto species by intramolecular hydrogen bonds because interactions of SAA with silanol groups are prevented. This is confirmed by the higher intensity of the fluorescence emission and fluorescence efficiency, as can be observed from Table 2, which is an important finding characterizing ESIPT molecules, as it was also observed by other authors [17,18]. However, when aromatic groups are present as organic modifiers in the structure of the network (G1, G4), π-π interactions with SAA molecules also take place, diminishing fluorescence intensity, by comparison with G0.…”
Section: Photophysical Properties Of Fluorescent Hybrid Materialssupporting
confidence: 85%
“…In these pores, there can be found aggregated SAA molecules, favoring the stabilization of cis-keto species by intramolecular hydrogen bonds because interactions of SAA with silanol groups are prevented. This is confirmed by the higher intensity of the fluorescence emission and fluorescence efficiency, as can be observed from Table 2, which is an important finding characterizing ESIPT molecules, as it was also observed by other authors [17,18]. However, when aromatic groups are present as organic modifiers in the structure of the network (G1, G4), π-π interactions with SAA molecules also take place, diminishing fluorescence intensity, by comparison with G0.…”
Section: Photophysical Properties Of Fluorescent Hybrid Materialssupporting
confidence: 85%
“…Representative spectra of RL for HBO dyes 1 – 3 and 5 are given in Figure 8a–d (and S7, Figure S7.4), while the integrated emission intensity dependence on the exciting energy density is presented in the log–log scale in Figure 8e–h. The RL studies on HBO 4 have been reported elsewhere [45]. The stimulated emission occurs above the threshold level of pumping energy density, as evidenced by a rapid increase of the emission intensity.…”
Section: Resultsmentioning
confidence: 99%
“…The random laser (RL) is a nonconventional laser whose feedback mechanism is based on random scattering . The first ESIPT-based random laser was reported in 2018 based on a novel designed 2-(2′-hydroxyphenyl)­benzoxazole (HBO) derivative with introducing two triethylsilylethynyl groups at the 3,5 positions of the phenol ring (for the chemical structure, see Figure a) Figure b showed the emission image of this newly designed molecule above the RL threshold.…”
Section: Recent Progress In Esipt-based Organic Lasersmentioning
confidence: 99%
“…(e) Dependence of the RL threshold on HBO concentration. Adapted with permission from ref . Copyright 2018 Royal Society of Chemistry.…”
Section: Recent Progress In Esipt-based Organic Lasersmentioning
confidence: 99%